PKM Kelompok Kerajinan Upia Karanji Bayalo Desa Motinelo Kecamatan Tabongo Kabupaten Gorontalo - Syamsul, Syamsul; Rahmatia, Rahmatia; Pakaya, Saiful (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2019)
One of the handicrafts in Gorontalo Province is Upia Karanji which is also commonly called the Kopiah Basket. This craft is a typical Gorontalo craft made from Mintu tree bark. During its development, various problems arose from the production process, business management, and marketing. The results of the implementation of the Community Partnership Program (PKM) of the solutions offered are in the aspect of production by selecting production support partners so that partners get at least 1 distributor of raw materials. Contribute to the production phase and the implementation of tools that can make time efficient at all stages of production, and the support of tools for partners continues to promote safety at work. Training and guidance on the preparation of financial statements so that partners have a simple financial accounting for their business. Organizational training is provided to partners so as to provide capabilities in and provide work based on the number of members. Design training and guidance for partners so that partners create products that have diverse motives. Marketing management training and promotion demonstrations to partners so partners can practice modern ways of promotion. Assistance with marketing partners so that partners get marketing partners who can increase sales.